The flight trajectory analysis on the existing aircraft - M Khalifa, Tarek M. (2012)
This thesis presents the flight trajectory analysis for a given aircraft configuration starting with aircraft set at trim condition and after that following by descent for landing. It has been known that the aircraft behaviors during their flight governed by the flight equation of motions. This flight equation of motion consist of 12 first order differential equations which coupling to each other. Those 12 equations described 12 state space variables involving the aircraft position plus aircraft aptitude with respect to the inertial coordinate system and also with respect to their axis body system which is had been used. In the stage of development in developing flight control on board, it is necessary to develop a computer code for solving the governing equation of flight motion for a given aerodynamic characteristics, control surfaces movement and aircraft’s mass with inertia properties to obtain their trajectory and also velocity at any instant time. The present work has presented the flight dynamics analysis for two aircraft models. The first aircraft model is Boeing 747 while the second one is the airplane designed to become UAV airplane after appropriate flight controller installed to that airplane. Through this work it can be conclude, in manner how to solve the governing equations are simpler compared to the effort for providing the aerodynamics data or the mass and inertia of the airplane. In the future the control law which represents the governing equation to set the control surface may be introduced in order to keep the airplane at constant speed or at constant altitude. This may the suggestion to modify the present computer code to become design tool for prescribing aircraft flight under a constant speed or constant altitude.